Kepastian Hukum Akta Jual Beli Hak Atas Tanah Bersertifikat Atas Hutang Piutang Yang Didasarkan Kuasa Mutlak - Erny Oktavina; Ramlani Lina Sinaulan; I Wayan Karya (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
The sale and buy agreement is a consensual agreement, meaning that the existence of an agreement between the parties is sufficient to constitute the contract. However, the land sale and purchase agreement stipulated by Law No. 5 of 1960 on Agrarian Principles is a valid contract because it is founded on customary law, which is cash, real, and unambiguous. The agreement between the seller and buyer of land rights, although the sale and purchase cannot be performed before the PPAT, must be stated in a contract, which in general, such legal activities are carried out in the presence of a notary. This research employs a normative legal methodology that is supplemented by interviews. According to the findings of the study, the position of absolute power serves as the basis for the sale and purchase of recognized land rights. Absolute power as the basis for the deed of sale and purchase of land rights can be exercised so long as it is an integral component of the sales agreement. Absolute authority results from the emergence of wants based on the principle of contract freedom, whose restrictions are outlined in Articles 1320 and 1338 of the Civil Code.